The Role of Microbial Enzymes in Organic Waste Bioconversion: A Biochemical and Renewable Energy Perspective - Anggraini, Welly (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This study explores the role of microbial enzymes in the bioconversion of organic waste into renewable energy sources such as bioethanol, biogas, and biohydrogen. Employing a qualitative literature review, this research applies a systematic thematic synthesis to 28 scientific sources, including journal articles, policy reports, and textbooks published between 2018 and 2024. The findings indicate that enzymes such as cellulase, amylase, and lipase play a dominant role in the hydrolysis of organic substrates, breaking down complex biomolecules into glucose, amino acids, and fatty acids. These hydrolysis products are then fermented anaerobically by microbes like Saccharomyces cerevisiae and Clostridium spp. to generate various bioenergy outputs. In addition, the study highlights the importance of biochemical characteristics such as enzyme kinetics, stability, and substrate specificity, which are critical for improving energy conversion efficiency. Operational challenges include high production costs and suboptimal enzyme performance under non-laboratory conditions. However, promising innovations have emerged, including enzyme immobilization techniques, co-fermentation strategies, and the use of genetically engineered microorganisms. Case studies from India, Germany, and Indonesia demonstrate the practical potential of microbial enzyme-based bioconversion systems in transforming agricultural and household waste into valuable energy products. The integration of microbial enzymes into waste management not only reduces environmental pollution but also supports clean energy transition efforts. This research implies the need for policy alignment and educational curriculum integration in environmental science to accelerate public adoption and awareness. This research implies the need for policy alignment and educational curriculum integration in environmental science to accelerate public adoption and awareness.